Ehrlichia chaffeensis Infections among HIV-infected Patients in Human Monocytic Ehrlichiosis–Endemic Area - Talbot, Thomas R. (Centers for Disease Control and Prevention, 2003)
Manifestations of human monocytic ehrlichiosis (HME), a tick-borne infection caused by Ehrlichia chaffeensis, range from asymptomatic disease to fulminant infection and may be particularly severe in persons infected with HIV. We conducted a serologic study to determine the epidemiology of HME in HIV-positive patients residing in an HME-endemic area. We reviewed charts from a cohort of 133 HIV-positive patients who were seen during the 1999 tick season with symptoms compatible with HME (n=36) or who were asymptomatic (n=97). When available, paired plasma samples obtained before and after the tick season were tested by using an indirect immunofluorescence assay (IFA) to detect antibodies reactive to E. chaffeensis. Two symptomatic incident cases were identified by IFA, resulting in a seroincidence of 6.67% among symptomatic HIV-positive participants with paired samples available for testing and 1.64% overall. The baseline seroprevalence of HME was 0%. In contrast to infection in immunocompetent patients, E. chaffeensis infection in HIV-positive persons typically causes symptomatic disease.